2018
DOI: 10.5826/dpc.0804a13
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma: variation in invasion depth by subtype, sex, and anatomic site in 4,565 cases

Abstract: BackgroundThe depth of invasion by basal cell carcinoma (BCC) subtypes varies.ObjectiveTo investigate BCC invasion depth variation by subtype and anatomic site.MethodA prospective consecutive case series of excised BCC from 2009 to 2014 in a single Australian clinic.ResultsDescending mean depths for a total of 4,565 BCC cases by subtype were as follows: nodulocystic, 1.9 mm (n = 84, 95% CI: 1.70–2.03, P = 0.66); nodular, 1.6 mm (n = 947, 95% CI: 1.53–1.63, P < 0.0001); aggressive, 1.5 mm (n = 925, 95% CI: 1.44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
3
16
0
4
Order By: Relevance
“…12,13,15,16 One study found the depth of tumour invasion of BCC presenting in men to be greater than BCC in women. 20 Our findings are consistent with the majority of the literature, which reports a disproportionately higher rate of BCC in men. In addition, we found the female sex to be protective against BCC with LSE.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…12,13,15,16 One study found the depth of tumour invasion of BCC presenting in men to be greater than BCC in women. 20 Our findings are consistent with the majority of the literature, which reports a disproportionately higher rate of BCC in men. In addition, we found the female sex to be protective against BCC with LSE.…”
Section: Discussionsupporting
confidence: 93%
“…It is generally thought that men will have more lifetime sun exposure than women, which will increase their risk of developing BCC; men participate in more outdoor sports and occupations, wear less sun protection, have a more significant history of sunburns and are less likely to seek prompt medical care . One study found the depth of tumour invasion of BCC presenting in men to be greater than BCC in women . Our findings are consistent with the majority of the literature, which reports a disproportionately higher rate of BCC in men.…”
Section: Discussionsupporting
confidence: 89%
“…The sex differences in keratinocyte carcinoma burden are likely multifactorial and could be related to sun safety behaviors, 31 health resource utilization, [32][33][34] and tumor stage at presentation. 34,35 Some of the trends in our data are comparable to those in other populations. Age-standardized malignant melanoma incidence rates in light-skinned individuals in the United States, Sweden, Australia, New Zealand, Norway, and the United Kingdom have been steadily increasing by 3% each year from 1982 to 2011 and are projected to increase through 2031.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since the pathologist assessed the cytology smears blindly with no knowledge of the clinical notes or the final histopathological diagnosis, an association of cytological patterns with BCC subtypes could not be made in advance. Moreover, the shaving biopsy may have missed some of the deepest BCC subtypes in the patients it was performed on [17,18]. Although dermoscopy was performed to exclude coexisting lesions, the location of most BCCs over photodamaged skin of the head and neck may hamper the recording of the squamous cell due to the background epidermal atypia [19].…”
Section: Discussionmentioning
confidence: 99%